Examining the Social-emotional Skills of TVET Educators and Students: A Dual Perspective Analysis - Dahri, Salma; Chinedu, Caleb Chidozie; Gull, Mehwish; Colcha Ortiz, Raquel Virginia (Journal of Technical Education and Training, 2024)
In Technical Vocational Education and Training (TVET), developing a skilled workforce is crucial. However, the effectiveness of TVET educators can be compromised by various challenges, including the insufficient understanding and integration of social-emotional skills (SES) into their scholarship and practice. Despite the importance of SES for enhancing educator efficacy and instructional quality, this area remains underexplored within the TVET context. This study, therefore, aims to evaluate the SES levels among TVET instructors and explore the differences in how instructors and students across various faculties perceive these skills. Additionally, it seeks to understand the impact of these perceptions on educational practices within TVET. Employing a quantitative case study design, this investigation compared the SES reported by 99 instructors and perceived by 373 final-year students, spanning both education and engineering faculties at Universiti Tun Hussein Onn Malaysia (UTHM). The findings reveal that both groups generally recognise high levels of SES among the instructors. Nevertheless, notable disparities exist between SES levels of educators from the education and engineering faculties, revealing significant disciplinary differences in social-emotional skill sets. The study underscores the pivotal role of SES in the TVET sector and highlights the necessity of external feedback in SES evaluation. By identifying disparities in SES perceptions across faculties, the study recognises opportunities for enhancing TVET instruction through targeted SES development, thereby potentially improving the efficacy and effectiveness of TVET educators.